The Influence of Learning Models and Motivation on Student Learning Outcomes in the Basic Science Concepts Course - Suleman, Suleman (Newinera Publisher, 2025)
This study aims to examine the impact of learning models and motivation on student learning outcomes in the Basic Science Concepts course within the Elementary School Teacher Education Program. The research employs an experimental method with a 2x2 treatment-by-level design involving two independent variables: learning models (STAD and TSTS) and motivation (high and low). A sample of 127 students was divided into four experimental groups. Learning outcomes were measured using a learning achievement test aligned with the course objectives. Data were analyzed using a 2x2 analysis of variance (ANOVA) to assess differences in learning outcomes based on these two factors, and Tukey's test was used to identify significant differences between groups. The ANOVA results indicated that the learning model had a significant effect with F = 4.09 (F table = 4.03), motivation had a very significant effect with F = 25.85 (F table = 4.03 and 7.17), and the interaction between learning models and motivation had a significant effect with F = 17.86 (F table = 4.03 and 7.17). Tukey's test revealed significant differences between experimental groups, particularly between the TSTS group with high motivation (A2B1) and the STAD group with high motivation (A1B1), with Q = 5.60 (Q table = 3.77). This study concludes that the TSTS model is more effective than STAD, especially for students with high motivation. Motivation plays a crucial role in enhancing learning outcomes, and it is essential for educators to align learning models with students' motivation levels.